2017
DOI: 10.5603/fm.a2017.0004
|View full text |Cite
|
Sign up to set email alerts
|

Circle of Willis variations and artery diameter measurements in the Turkish population

Abstract: Circle of Willis variations may show geographic and ethnic differences. Knowledge of the frequency and types of variation in the population is important for neurosurgeons and in radiological interventional procedures as a guide for entry and in respect of collateral which could develop later.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
23
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 5 publications
(11 reference statements)
4
23
1
2
Order By: Relevance
“…We found that variations were more frequent in the posterior circulation, the PCoA was the most variable artery, and the most common change was hypoplasia, followed by accessory vessels and arteries with atypical origin. Our results are in line with those of previous studies conducted on larger numbers of cadaveric specimens (21,23,24,30,32), and in vivo studies using magnetic resonance (MR) (19,22,39), or computed tomography (CT) angiography (41). In previous imaging-based studies, the frequency of absent vessels was higher than in our study and other previous cadaveric studies.…”
Section: █ Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We found that variations were more frequent in the posterior circulation, the PCoA was the most variable artery, and the most common change was hypoplasia, followed by accessory vessels and arteries with atypical origin. Our results are in line with those of previous studies conducted on larger numbers of cadaveric specimens (21,23,24,30,32), and in vivo studies using magnetic resonance (MR) (19,22,39), or computed tomography (CT) angiography (41). In previous imaging-based studies, the frequency of absent vessels was higher than in our study and other previous cadaveric studies.…”
Section: █ Discussionsupporting
confidence: 92%
“…The diameters of the arteries provided by our study are consistent with those of other cadaveric studies (22), but they are not comparable with those of imaging studies as we measured outer diameters whereas imaging studies measure the diameter of the blood column. Except for the ICA, the diameters in our study are almost double-sized compared to those reported in a previous MR angiography study (39). Since our study was conducted on cadaver brains without cerebrovascular pathology, a direct link between the modified geometry and the appearance of neurological pathology could not be demonstrated.…”
Section: █ Discussioncontrasting
confidence: 65%
“…The proximal segment of anterior cerebral artery (A1) supplies the basal surface of the cerebral hemisphere. The diameter of A1 according to Kamath et al [10], 2.3 mm for diameter and 14.25 mm length, Iqbal et al [8] diameter 2.3 mm and length 12.4 mm, on Turkish population length of A1 is 14.4 mm [11] while diameter 1.58 mm in the right A1, 1.64 mm in the left A1 [18], in Kosovo's population the diameters of A1 was 2.09 mm while length 13.96 mm [16]. In our study the diameter of ACA was 2.05 and length 14.01 mm.…”
Section: Discussionmentioning
confidence: 99%
“…Typical vessel sizes and past CFD simulations were considered when deciding on vessel diameters and idealized geometries used in this study [12][16] [20][21]. Models were constructed similarly in a commercially available CAD software.…”
Section: Vessel Representationmentioning
confidence: 99%